Learning from Local Wisdom: Friction Damper in Traditional Building - Lumantarna, B.; Pudjisuryadi, P. (Institute of Research and Community Outreach - Petra Christian University, 2012)
Indonesia is situated in the so called “Ring of Fire” where earthquake are very frequent. Despite of all the engineering effort, due to the March 28, 2005 strong earthquake (8.7 on Richter scale) a lot of modern buildings in Nias collapsed, while the traditional Northern Nias house (omohada) survived without any damage. Undoubtedly many other traditional buildings in other area in Indonesia have survived similar earthquake. Something in common of the traditional building are the columns which usually are not fixed on the ground, but rest on top of flat stones. In this paper some traditional building are subjected to non linear time history analysis to artificial earthquake equivalent to 500 years return period earthquake. This study shows that apparently the columns which rest on top of flat stone acts as friction damper or base isolation. The presence of sliding at the friction type support significantly reduces the internal forces in the structure.